"An Unchangeable Reason for inequality" A Qualitative Study on Nursing Students' Experiences and Perceptions of Menstruation and Menstrual Poverty - İlknur Atasever; Merve Mert Karadaş; Fatma Uslu Şahan; Gülten Koç (Galenos Publishing House, 2024)
Objective: Menstrual poverty is a significant issue in Turkey and worldwide and is influenced by various factors. It is crucial for nursing students to understand how to eliminate gender inequality caused by menstrual poverty. The study aims to explore student nurses' experiences and perceptions of menstruation and menstrual poverty. Method: The study utilized a phenomenological qualitative method and analyzed the data using descriptive analysis. Results: Based on the data gathered, five primary themes were identified: Thoughts on menstruation, experiences on menstruation, stereotypes about menstruation, management of the menstrual process, and things to be done to improve menstrual poverty. Conclusion: By educating individuals about menstruation, we can enhance their awareness and contribute to the elimination of menstrual poverty. Therefore, it is essential to implement interventions aimed at reducing menstrual poverty.